Characterization of the biological activities and physicochemical characteristics of recombinant bovine interferon-α14. Issue 1 (March 2015) - Shao, Jianwei; Cao, Chong; Bao, Jun; Gao, Mingchun; Wang, Junwei
Highlights We amplified a BoIFN-α gene from bovine liver genomic DNA and named it as BoIFN-α14. A recombinant mature BoIFN-α14 was expressed in the yeast Pichia pastoris. The biological activities and physicochemical characteristics of BoIFN-α14 were determined. BoIFN-α14 could inhibit the CPE of VSV, and could inhibit cell proliferation. BoIFN-α14 has the typical characteristics of IFN-α.